Enrichment of halotolerant hydrogen-oxidizing bacteria and production of high-value-added chemical hydroxyectoine using a hybrid biological–inorganic system - Feng, Xiang; Kazama, Daichi; He, Sijia; Nakayama, Hideki; Hayashi, Takeshi; Tokunaga, Tomochika; Sato, Kozo; Kobayashi, Hajime (Frontiers in Microbiology, 2023)
Hybrid biological–inorganic (HBI) systems show great promise as CO2 conversion platforms combining CO2 fixation by hydrogen-oxidizing bacteria (HOB) with water splitting. Herein, halotolerant HOB were enriched using an HBI system with a high-ionic-strength medium containing 180 mM phosphate buffer to identify new biocatalysts. The reactors were inoculated with samples from saline environments and applied with a voltage of 2.0 V. Once an increase in biomass was observed with CO2 consumption, an aliquot of the medium was transferred to a new reactor. After two successive subcultures, Achromobacter xylosoxidans strain H1_3_1 and Mycolicibacterium mageritense strain H4_3_1 were isolated from the reactor media. Genome sequencing indicated the presence of genes for aerobic hydrogen-oxidizing chemolithoautotrophy and synthesis of the compatible solute hydroxyectoine in both strains. Furthermore, both strains produced hydroxyectoine in the reactors under the high-ionic-strength condition, suggesting the potential for new HBI systems using halotolerant HOB to produce high-value-added chemicals.